EFFECT OF ACACIA NILOTICA LEAVES EXTRACT ON HYPERGLYCAEMIA, LIPID PROFILE AND PLATELET AGGREGATION IN STREPTOZOTOCIN INDUCED DIABETIC RATS - Asad, Munazza; Aslam, Muhammad; Munir, Tahir Ahmad; Nadeem, Amina (Journal of Ayub Medical College Abbottabad, 2011)
Background: To consider new hypoglycaemic, anti-hyperlipidaemic and anti-platelet aggregation sources, aqueous methanol extract of Acacia Nilotica (AN) leaves was investigated in streptozotocin induced diabetic rats. Methods: Diabetes mellitus was induced in 90 out of 120 male albino rats by administering 50 mg/Kg bodyweight (bw) streptozotocin intraperitonealy, and was confirmed by measuring fasting blood glucose level >200 mg/dL on 4th post-induction day. The rats were equally divided into 4 groups, A (normal control), B (diabetic control), C (diabetics rats treated with plant extract) and group D (diabetics rats treated with glyburide). The rats of group C and D were given single dose of 300 mg/Kg bw, AN extract, and 900 µg/Kg bw glyburide respectively for 3 weeks. Blood glucose levels were measured by glucometer, platelet aggregation by DiaMed method, Î²- thromboglobulin and insulin by ELISA technique, and lipid components were measured by enzymatic calorimetric method. Results: Significant differences (p<0.05) were noticed in blood glucose, serum insulin, platelet aggregation and triglyceride levels in diabetic rats treated with AN extract and glyburide as compared to diabetic controlled rats. A significant difference (p<0.05) in Î²- thromboglobulin and LDL levels was also noticed in rats treated with glyburide than the diabetic controlled rats. The levels of fasting blood glucose, Î²-thromboglobulin and platelet aggregation were significantly reduced (p<0.05) in diabetic rats treated with glyburide than AN extract treated rats. Conclusions: Administration of AN leaves extract showed hypoglycaemic and anti-platelet aggregation activity in diabetic rats as that of glyburide. Keywords: Acacia Nilotica, Hypoglycemia, Streptozotocin